2018
DOI: 10.1111/1541-4337.12382
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Future Prospects of Enzyme‐Based Biofilm Prevention Approaches in the Food Industry

Abstract: Food poisoning and foodborne diseases are a growing public health concern worldwide. Approximately 30 known and many unknown pathogens are the main culprits for these conditions. Biofilms are a heterogeneous living‐form of pathogens and are considered a safe haven for their pathogenicity. In the field of food processing, the persistence of biofilms results in an increased likelihood of food contamination, which ultimately compromises overall food quality and safety. Because of the robust heterogeneity and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 219 publications
0
50
0
8
Order By: Relevance
“…Enzymatic activity is dependent on pH and is sensitive to temperature, so this can limit its large scale application (Allie, Jacobs, Maartens, & Swart, 2003). In fact, temperature, pH, and exposure time are some of the important environmental factors that interfere with the activity and specificity of enzymes (Nahar et al, 2018). Furthermore, each enzyme requires an optimum temperature to exhibit their maximum activity and if there is a combination of enzymes it is important to establish the temperature that is closest to the optimal activity of each enzyme employed (Haki & Rakshit, 2003).…”
Section: Evaluation Of the Biofilm By The Culture Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enzymatic activity is dependent on pH and is sensitive to temperature, so this can limit its large scale application (Allie, Jacobs, Maartens, & Swart, 2003). In fact, temperature, pH, and exposure time are some of the important environmental factors that interfere with the activity and specificity of enzymes (Nahar et al, 2018). Furthermore, each enzyme requires an optimum temperature to exhibit their maximum activity and if there is a combination of enzymes it is important to establish the temperature that is closest to the optimal activity of each enzyme employed (Haki & Rakshit, 2003).…”
Section: Evaluation Of the Biofilm By The Culture Methodsmentioning
confidence: 99%
“…These results agree with a similar study by Molobela et al (2010), who observed that enzymatic treat- in contrast to some chemical disinfectants, the antibacterial effects of enzymes employed as cleaning agents is perceptible within minutes of exposure. This matter, however, is under discussion (Nahar et al, 2018) and is a further reason for continuing to research in this area.…”
Section: Evaluation Of the Biofilm By The Culture Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite that lysozyme has been immobilized in several support materials for microbial control (Bosio, Islan, Martínez, Durán, & Castro, 2016;Nahar, Mizan, Ha, & Ha, 2018), reports on immobilized lysozyme referred to its application in wine stabilization are few. Immobilization by covalent attachment to solid supports has been the preferred strategy, as in the case of other enzymes used in winemaking.…”
Section: Immobilized Lysozyme For Wine Microbial Stabilizationmentioning
confidence: 99%